1999
DOI: 10.1021/op9900683
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Development of the Commercial Route to Sildenafil:  A Case History

Abstract: This paper is a case history of the chemical development of sildenafil which covers various aspects of work in chemical development namely: route selection, scale-up issues, the development of an efficient synthesis with high throughput, process safety, and environmental issues. Interesting chemical points include improved methods of preparing pyrazolo[4,3-d]pyrimidines and the unusual isolation of an intermediate as its double salt (10). The potential dangers of nitrating pyrazole-5-carboxylic acids which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(107 citation statements)
references
References 5 publications
(5 reference statements)
1
100
0
1
Order By: Relevance
“…Indeed, one of the intermediates or side products may become the dominant product, for instance, azoxy, hydrazo and hydroxylamines can be in high yields [4,22,24]. The accumulation of hydroxylamines is dangerous, explosive even at low levels, as these compounds are thermodynamically unstable [26].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, one of the intermediates or side products may become the dominant product, for instance, azoxy, hydrazo and hydroxylamines can be in high yields [4,22,24]. The accumulation of hydroxylamines is dangerous, explosive even at low levels, as these compounds are thermodynamically unstable [26].…”
Section: Introductionmentioning
confidence: 99%
“…N-Acyl imidazole intermediates are known to react with a wide range of primary and secondary amines and have been shown to be tolerant of the presence of a number of different functional groups, 13 enabling their use for the synthesis of pharmaceutical intermediates on an industrial scale ( Figure 15(b)). 87 Interestingly, Batey and coworkers have recently demonstrated that structurally related N-carbamoylimidazolium salts derived from secondary amines are highly effective reagents for converting acids into secondary amides (Figure 15(c)). 88 Nucleophilic catalysts such as 1,8-diazabicyclo [5.4.0]undec-7-ene (DBU) have also been employed to improve the yields of amide bondforming reactions using N-acyl imidazoles as coupling agents, particularly for the acylation reactions of sterically hindered acids and electron-poor anilines ( Figure 16).…”
Section: N-acyl Transfer Reagentsmentioning
confidence: 99%
“…Aryl(heteroaryl)sufones were available using an S N Ar-type process. [25] Accordingly, reaction of 2 g with 2-chlorobenzothiazole provided the corresponding heterocyclic sulfone (7). Treatment of the ammonium sulfinate with sulfuryl chloride resulted in oxidative chlorination and allowed isolation of the derived sulfonyl chloride (8).…”
Section: Angewandte Chemiementioning
confidence: 99%